Réponses

2014-04-21T20:25:07+02:00
Bonsoir
Tu mets sous même dénominateur
a .
   7 y + 45 = 72
7y = 72 - 45
7y= 27
y = 27/7

b. 
x - 32 = 10
x = 10 +32
x = 42

c. 
6x - 9 = 16
6x = 16 +9
6x = 25
x = 25/6

d.

3/7 y - 1/7 = - 8/14
6y - 2 = -8
6y = -8 +2
6y = -6
y = -1

2014-04-21T20:34:17+02:00
Résoudre les équations suivantes :

a.
7 y + 45 = 72
7y = 72 - 45
7y = 27
y = 27/7

b. 
x - 32 = 10
x = 10 + 32
x = 42

c. 
6x - 9 = 16
6x = 16 + 9
6x = 25
x = 25/6

d.

3/7 y - 1/7 = - 8/14
3 x 2 / 7 x 2y - 1 x 2 / 7 x 2 = - 8/14
6/14y - 2/14 = - 8/14
6y - 2 = -8
6y = -8 + 2
6y = - 6
y = - 6/6
y = -1